Screening for Inherited Metabolic Disorders by Tandem Mass Spectrometry May Miss L-2 Hydroxy Glutaric Aciduria: A Report of Two Cases - Baskar, Dipti; Nashi, Saraswati; P., Srijithesh Rajendran; Arunachal, Gautham; Christopher, Rita; Kulkarni, Girish B.; Alladi, Survarna (Journal of Pediatric Neurology, 2021)
L-2 hydroxy glutaric aciduria (L-2HGA) is an autosomal recessive neurometabolic disorder. It is characterized by a variety of clinical features and typical radiological features which aids in diagnosis. We report two cases that presented with unexplained intellectual impairment and seizures. Magnetic resonance imaging (MRI) brain showed characteristic features of L-2HGA. Tandem mass spectrometry was negative in both cases. Genetic analysis was done based on typical imaging features which confirmed the diagnosis of L-2HGA. For patients with unexplained developmental delay and typical MRI features, a high degree of suspicion is necessary to confirm the diagnosis with targeted genetic analysis.
Keywords: L-2 hydroxy glutaric aciduria; seizures; status dystonicus; tandem mass spectrometry